A Systematic Review and Meta-analysis on the Average Age of Menopause among Iranian Women - Marzieh Saei Ghare Naz; Fatemeh Sayehmiri; Faezeh Kiani; Giti Ozgoli (Journal of Evidence-Based Care, 2019)
Background: Menopause age is a determinant of health status and the risks for future diseases. Aim: The current study aimed to determine the average age of menopause among Iranian women in a meta-analysis. Method: This systematic review and meta-analysis was performed in August 2017. The articles were searched in Persian databases, including Iran Medex, SID, and Magiran, as well as international databases, including Scopus, PubMed, and Web of Knowledge, without any time limitation. The search process was accomplished using the following keywords: “Menopause” OR “Menopause age” OR “Age of menopause” OR “Menopause age and Iran”. Begg’s and Egger tests were used to identify publication bias. Data analysis was performed in Stata statistical software (version 14) using random effect model. Results: The search process resulted in the inclusion of 28 articles with a total of 40,042 subjects published during 1998-2017. The mean age of menopause was evaluated as 48.57 years (CI: 47.96- 49.18). Analysis of subgroups indicated that the mean ages of menopause were evaluated as 47.21 (CI: 46.94-47.48), 48.43 (CI: 47.76-49.10), 47.53 (CI: 47.17-47.88), 47.80 (CI: 47.49-48.11), and 47.83 (CI: 47.34-48.32) in smoking women (based on nine studies), non-smoking women, women with normal body mass index (based on eight studies), overweight women (based on seven studies), and obese women (based on six studies), respectively. The minimum mean age was 47.97 years, which belonged to the north region. Implications for Practice: The results suggested that the average age of menopause is still within a normal range despite its rise with a normal slope. It seems that the changes in the women’s lifestyle have affected the menopause age. Consequently, special attention should be paid to some factors confounding menopause age among Iranian women to promote their health and reduce the health problems related to menopause.